Natural Crystal Structure for Generating Raman‐Like Orbital Angular Momentum States - Tianxiang Meng; Changsheng Zheng; Yongguang Zhao; Haohai Yu; Huaijin Zhang (Advanced Science)
Abstract Creation of structured light at‐source with determinate orbital angular momentum (OAM) states is a fascinating branch of modern optics, owing to their integrability, wavelength insensitivity, and high mode purity. However, mode degeneracy in spatially column‐symmetric cylindrical coordinate systems leads to a total zero OAM states which seriously limits their development and applications. Here, a strategy is proposed for symmetry breaking of the degenerate OAM states relying on the natural anisotropy of crystal gain, to select the handedness of the spatial spiral phase front and further tunable Raman‐like OAM states by thermal‐driven, experimentally realized arbitrary OAM states from −2ћ to ћ. The concept presented herein clarifies the contribution of intrinsic crystal property to the OAM states and opens a new route for an at‐source solution of structure light with high integrability and controllable OAM states.